2016
DOI: 10.5194/soil-2015-84
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Calculating the sediment budget of a tropical lake in the Blue Nile basin: Lake Tana

Abstract: Soil erosion decreases soil fertility of the uplands and causes siltation of lakes and reservoirs. However, very little data exists to quantify accurately the impact of sediment on lakes in tropical monsoonal areas in the African highlands. Lake Tana is one of these lakes in Ethiopia. The objective of this study is to quantify the sediment budget for Lake Tana watershed with limited observational data. To overcome these limitations we use the Parameter Efficient Distributed (PED) model that has shown to perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 28 publications
3
19
2
Order By: Relevance
“…Moreover, the mean sediment trapping efficiency ( T e ) of Lake Tana was also calculated from the measured sediment fluxes as 97%. This value is higher than the T e of 50% used in the Abay Basin Master Plan Study (BCEOM, ), but is consistent with the higher values documented by other authors (SMEC, ; Engida, ; Maes, ; Zimale et al, ).…”
Section: Resultssupporting
confidence: 91%
“…Moreover, the mean sediment trapping efficiency ( T e ) of Lake Tana was also calculated from the measured sediment fluxes as 97%. This value is higher than the T e of 50% used in the Abay Basin Master Plan Study (BCEOM, ), but is consistent with the higher values documented by other authors (SMEC, ; Engida, ; Maes, ; Zimale et al, ).…”
Section: Resultssupporting
confidence: 91%
“…Khelifa et al (2016) reported daily runoff with NSE values of 0.64 for calibration and 0.68 for validation. Similar studies are in better agreement with these results (Addis et al 2016;Zimale et al 2016). For a study in the Gumara watershed by Zimale et al (2016), the NSE values for daily flows obtained were 0.70 for calibration and 0.77 for validation period.…”
Section: Runoff Calibration and Validationsupporting
confidence: 80%
“…These authors report NSE values for runoff simulations using SWAT of 0.64 and 0.68 for calibration and validation, respectively. In another study in the Gumara watershed by Zimale et al (2016), the NSE values for daily flows obtained were 0.70 for calibration and 0.77 for validation period, which is comparable with the UW and TW NSE values in the Gumara-Maksegnit watersheds. However, the model tends to underestimate sediment yield during calibration and validation periods for both watersheds.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations